2004
DOI: 10.1002/j.2050-0416.2004.tb00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Malting Behaviour of Barleys Grown in Canada and Spain as Related to Hordein and Enzyme Content

Abstract: To continue our effort to analyse the genetic (varietal) and environmental (sites and years) effects on malting quality of barley, we have field‐tested four barley varieties, two‐ and six‐rowed, European and North American, in Spain and Canada in 1998 and 1999. The Spanish trials were autumn‐sown whereas the Canadian ones were spring‐sown. Barley grain was analysed for total protein and hordein contents and micromalted. Canadian‐grown barleys had significantly lower contents of grain protein and all‐three hord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The weight loss during the malting process showed that even though the steelier samples had a higher respiration rate and a higher total malting loss, the growth of their rootlets was lower than in the mealy samples. Recently, low respiratory losses have been linked to a low grain protein content (26), but our results suggest that endosperm structure may also affect respiratory losses. Apparently the high respiration rate of steelier barley was not related to the growth of the embryo but possibly to an increased requirement of energy for endosperm degradation caused by the tight structure of endosperm.…”
Section: Discussioncontrasting
confidence: 49%
“…The weight loss during the malting process showed that even though the steelier samples had a higher respiration rate and a higher total malting loss, the growth of their rootlets was lower than in the mealy samples. Recently, low respiratory losses have been linked to a low grain protein content (26), but our results suggest that endosperm structure may also affect respiratory losses. Apparently the high respiration rate of steelier barley was not related to the growth of the embryo but possibly to an increased requirement of energy for endosperm degradation caused by the tight structure of endosperm.…”
Section: Discussioncontrasting
confidence: 49%
“…1993), which could have affected six‐row types, particularly the lateral florets, to a greater extent, as even six‐row progeny had high levels of protein compared with all lines at the other sites. The malting quality of Spanish‐grown barley can be comparable to, or better than, that of N. European or Canadian barley, despite higher protein levels (Molina‐Cano et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Further, Veliz et al ( 21 ) observed an increase in the expression of hordein C (poor in sulphur) due to the effect of nitrogen fertilisation. In contrast, Molina Cano et al ( 14 ) , in a series of field trials in Spain and Canada, together with Savin et al ( 22 ) in a container experiment observed no change in the proportion of the different hordeins due to nitrogen fertilisation.…”
Section: Introductionmentioning
confidence: 92%
“…The two most abundant fractions are B (rich in sulphur) and C (poor in sulphur), while the two less abundant fractions are D (intermediate sulphur content) and gamma (sulphur rich, high molecular weight) ( 11 ) . When different cultivars ( 12 ) or grains of the same cultivar grown in different geographical regions were compared ( 13, 14 ) , malt extract was positively related to the ratio of B‐hordein to C‐hordein. However, this relationship has not always been corroborated ( 15 ) .…”
Section: Introductionmentioning
confidence: 99%